2016
DOI: 10.1038/eye.2016.32
|View full text |Cite
|
Sign up to set email alerts
|

Reply to ‘Comment on: Long-term outcomes of neovascular glaucoma treated with and without intravitreal bevacizumab’

Abstract: Another aspect of NVG prevention is represented by treating the patients with central/hemi-CRVOs in whom ocular neovascularization already has appeared but IOP still remains within normal limits (eg, the preglaucomatous stage of NVG 2 ). In such cases we administer IVB injections, topical steroids, and cycloplegics; unless the neovascularization subsides with these treatments, we promptly apply panretinal photocoagulation that may prevent or delay any developing of the intractable sightthreatening NVG.In concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It is well known that immune cells such as T and B lymphocytes are crucial in the pathogenesis and development of RA and are involved in the activation of immune cells and secretion of multiple cytokines. Furthermore, recent studies have shown that IKZF3 is associated not only with RA [49][50][51] but also with other autoimmune diseases [41,[52][53][54] .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that immune cells such as T and B lymphocytes are crucial in the pathogenesis and development of RA and are involved in the activation of immune cells and secretion of multiple cytokines. Furthermore, recent studies have shown that IKZF3 is associated not only with RA [49][50][51] but also with other autoimmune diseases [41,[52][53][54] .…”
Section: Discussionmentioning
confidence: 99%